INTENSI KOMPLAIN KONSUMEN DITINJAU DARI SIKAP ASERTIVITASNYA - Fatma, Anne (Universitas Sahid Surakarta, 2012)
Consumers complain is disappointing expression toward industry. This research aimed to find the correlation between assertively and consumers complain intensity. The hypothesis is to find correlations between assertively and consumers complain intensity of students. The population is students who stay in Yogyakarta. The sample is taken with random sampling, the collecting data methods used assertively scale and consumers complainÂ intensity scale. The data analysis with product moment analysis shows that there is significant correlation between assertively and consumers complain intensity. The result is r=0.734 and p=0.000 (p<0.01), that means there are positive correlation betweenÂ assertively and consumers complain intensity; more assertively and doing so consumers complain intensity. The assertively aspects can be good predictor of consumers complain intensity.